2016
DOI: 10.4274/tnd.68889
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adult Hippocampal Neurogenesis in Learning and Memory Function

Abstract: Adult hippocampal neurogenesis is the lifelong production of new functional neurons from neural stem cells in the adult brain. Production of neurons in the adult brain is limited to two areas. One of these is the subgranular region in the hippocampus dentate gyrus (DG), the other is the subventricular zone of the lateral ventricles. New neurons produced in the hippocampus DG functionally integrate into mature circuits, and contribute to cognition and emotional control, learning and memory functions in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Neuroplasticity depends on two distinct but interrelated phenomena that contribute to adaptation and life -long learning: neuro-genesis (and synaptogenesis) and brain rewiring. It has been found that new neurons in the hippocampus dentate gyrus contribute to cognition, emotional control, learning and memory, the core components of adaptation [64]. Consciousness influences brain adaptability both during wakefulness as well as during sleep in a top down way.…”
Section: 5mentioning
confidence: 99%
“…Neuroplasticity depends on two distinct but interrelated phenomena that contribute to adaptation and life -long learning: neuro-genesis (and synaptogenesis) and brain rewiring. It has been found that new neurons in the hippocampus dentate gyrus contribute to cognition, emotional control, learning and memory, the core components of adaptation [64]. Consciousness influences brain adaptability both during wakefulness as well as during sleep in a top down way.…”
Section: 5mentioning
confidence: 99%
“…Mostly, T3 in cerebral tissue is locally produced through the conversion from T4. Besides, L-T4 administration raises both serum and cerebral concentrations of free T4 and T3 (26).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, damage to the hippocampus can result in spatial memory disorders. Dysfunctions in neurotransmitters and disturbances in GABA and adenosine concentrations, as well as redox systems in the CNS caused by THs dysfunction, can hinder neurogenesis and CNS growth (26). Therefore, maintaining stable concentrations of THs can help prevent the development of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%